Viability and survival of mango scions, Mangifera indica, as affected by different concentrations of Anaa at varying storage duration. - Petrola, Henry (UPHSI, 2003)
Mango, Mangifera indica, is one of the major export fruits of the Philippines. There is a need to expand mango plantation to cope with the demands of both local and international markets. The viability and survival of scions are one of the problems of the plant propagators when transporting due to long storage duration before grafting is done. This study aims to determine the effect of different concentrations of Alpha Naphthalene Acetic Acid (ANAA) and the different storage duration for the development of the mango scions. This study was conducted in a split-plot design using untreated scions and scions treated with different concentrations of ANAA (0, 100, 150, 200, 250, 300 ppm) stored at various storage durations (5, 10, 15 days). This study was conducted for the duration of 30 days. Results showed that high viability of scions after storage was observed at scions treated with 100 ppm at five days storage. High viability as also observed at 100 ppm at five days storage for dat taken five, ten, fifteen days after grafting. Significant percent survival and developmental stages were observed in scions treated with pure water and stored for five days before grafting. This data was taken fifteen days after grafting. Untreated scions stored for five days showed earlier bud emergence. There was high mortality of scions at ten and fifteen days storage. There were no fully developed leaves for all the treatment towards the end of the study duration.